1996
DOI: 10.1038/ki.1996.401
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular abnormalities in children, adolescents and young adults with renal disease

Abstract: The cardiac abnormalities that complicate chronic renal failure and renal replacement therapy are not well characterized in young people. These abnormalities are becoming more important because successful renal transplantation has resulted in children with end-stage renal failure living longer. Echocardiographic abnormalities of cardiac function and structure were studied in children and young adults (< 27 years old) with chronic renal failure (CRF, N = 32), end-stage renal failure treated with chronic periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
127
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 39 publications
13
127
4
1
Order By: Relevance
“…[1][2][3][4][5]16 Previous cross-sectional analysis in the CKiD cohort (n=366) reported a 17% prevalence of LVH at baseline. 2 Our present longitudinal study, in a larger population (n=478), showed similar prevalence of LVH at baseline (V2) of 16%.…”
Section: Prevalence Of Lvhmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5]16 Previous cross-sectional analysis in the CKiD cohort (n=366) reported a 17% prevalence of LVH at baseline. 2 Our present longitudinal study, in a larger population (n=478), showed similar prevalence of LVH at baseline (V2) of 16%.…”
Section: Prevalence Of Lvhmentioning
confidence: 99%
“…[1][2][3][4][5] Some data in children with CKD suggest that the development of LVH is associated with other cardiac abnormalities, such as impaired systolic function. [6][7][8][9] Thus, understanding the factors that contribute to LVH in children with CKD may lead to interventions to reduce future cardiovascular risk.…”
mentioning
confidence: 99%
“…3 In contrast, systolic LV function is thought to be preserved in children with chronic renal failure. 1,4,5 However, these studies have examined LV systolic performance at rest, and it is possible that evaluation during exercise may unmask more subtle changes in LV function.…”
mentioning
confidence: 99%
“…Echocardiographic studies show that young patients with chronic renal insufficiency (CRI) and end-stage renal disease have abnormalities of both left ventricular (LV) structure and function. [1][2][3][4][5] Children with chronic renal disease have a high prevalence of left ventricular hypertrophy (LVH). 1,6 -10 In adults with hypertension and chronic renal failure, LVH is thought to be initially adaptive to improve contractility and lower wall stress (WS) in the face of increased afterload (blood pressure) and preload (volume).…”
mentioning
confidence: 99%
“…The need to recognize and investigate dyslipidemia after transplantation is related to the well known observation that even in children, cardiovascular diseases are responsible for over 40% of all mortality in the setting of ESRD (26). Although the risk of cardiovascular mortality decreases significantly after transplantation, it continues to account for about 10% of all deaths in the post-transplant period (27).…”
Section: Discussionmentioning
confidence: 99%